The Rise of Low-Code/No-Code Development: Democratizing Application Development - Balaji Bodicherla (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
The emergence of low-code and no-code development platforms has fundamentally transformed the software development landscape, offering organizations innovative approaches to application development. These platforms have significantly impacted various sectors, from large enterprises to small and medium-sized businesses, particularly in accelerating digital transformation initiatives. Adopting these platforms has shown remarkable benefits in terms of development efficiency, cost reduction, and business agility while presenting important considerations regarding governance, security, and technical limitations. As organizations increasingly embrace these technologies, the market has shown substantial growth, driven by the demand for rapid application development and business process automation, with cloud-based deployments becoming the preferred choice for implementation.